Research Progress of Tumor-associated Neutrophils in the Occurrence and Development of Lung Cancer - Xiaoyan LI; Jianjun ZHOU; Chaoting ZHAO; Yudi ZHANG (Chinese Journal of Lung Cancer)
Lung cancer is the malignant tumor with the highest mortality rate worldwide. The tumor microenvironment (TME) is a key factor in the progression of lung cancer, composed of tumor cells, signaling molecules, fibroblasts, immune cells, etc. Among them, tumor associated neutrophil (TAN), as an important component of immune cells in the TME, plays multiple roles in tumor cell proliferation, invasion, angiogenesis, and metastasis due to its aberrant function, and is closely associated with poor prognosis. However, there are limited researches on the mechanism of TAN in lung cancer. This review aims to provide more scientific basis for studying the therapeutic targets of lung cancer and developing new drugs by elucidating the different subtypes of TAN and their mechanisms of action in the occurrence and development of lung cancer.